Pemetaan Kualitas Airtanah Berdasarkan Parameter Total Dissolved Solid (TDS) dan Daya Hantar Listrik (DHL) dengan Metode Ordinary Kriging Di Kec. Padang Barat, Kota Padang, Provinsi Sumatera Barat - M Asy Ruseffandi; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2020)
Abstarct. The overuse of groundwater with the management of water sourcesthat ignores the environment can decrease the quantity and quality ofgroundwater. In the area of West Padang, groundwater quality degradation iscaused by the dynamics of development West Padang towards the profile ofMetropolitan City. The purpose of this research is to make the water quality zonemap based on DHL and TDS parameter, zone map based on decrease ofgroundwater level and predict the occurrence of seawater intrusion in the WestPadang. The research method used is to identify the quality groundwater and adecrease of groundwater level from water analysis using Kepmen ESDM Nomor1451.K/10/MEM/2000 and make the distribution of water quality and a decreaseof groundwater level using the software SGeMs and ArcMap GIS 10.5, andpredict patterns spread of seawater intrusion from water quality analysis usingthe regression equation. From the identification result and analysis of waterquality, West Padang is categorized as a safe zone. Safe zone is the area thatmeets one of decrease criteria on groundwater quality which are characterizedby the increase of TDS that is less than 1,000 mg/l or less than 1,000 DHLμmhos/cm.Keywords:.TDS, DHL, Safe Zone, Groundwater Quality